Analisis Standarisasi Laboratorium Biologi di SMA Negeri 6 Pematangsiantar - Melisa, Melisa; Silalahi, Mastiur Verawaty (Lembaga Yasin AlSys, 2024)
Learning must have supporting infrastructure, where laboratory rooms have an important role in supporting an orderly learning or education process. The purpose of this research was to determine the standardization of biology laboratories at SMA Negeri 6 Pematangsiantar. This research uses descriptive research methods using a quantitative approach with research subjects of 36 class XI students. Data collection techniques use observation and questionnaires. The data analysis technique used by researchers in this research is the Guttman scale. The research results show that the data from research on the standardization of biology laboratories at SMA Negeri 6 Pematangsiantar can be said to be feasible, because the average percentage obtained from the results of the questionnaire data shows that the laboratory has very good standards, namely with a percentage of 99.98%.